2017
DOI: 10.1111/jcmm.13206
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib reduces ventilation‐augmented bleomycin‐induced epithelial–mesenchymal transition and lung fibrosis through suppression of the Src pathway

Abstract: Mechanical ventilation (MV) used in patients with acute respiratory distress syndrome (ARDS) can increase lung inflammation and pulmonary fibrogenesis. Src is crucial in mediating the transforming growth factor (TGF)‐β1‐induced epithelial–mesenchymal transition (EMT) during the fibroproliferative phase of ARDS. Nintedanib, a multitargeted tyrosine kinase inhibitor that directly blocks Src, has been approved for the treatment of idiopathic pulmonary fibrosis. The mechanisms regulating interactions among MV, EMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 50 publications
1
62
0
1
Order By: Relevance
“…Src kinase has previously been shown to be required for bcatenin phosphorylation at tyrosine residue 654 (Y654) and the initiation of EMT, and it has been correlated with increased b-catenin-dependent transcription in both A549 cells and primary AECs (Kim et al, 2009;Ulsamer et al, 2012). As mentioned previously, nintedanib significant inhibits Src family kinases (Li et al, 2017). Thus, we suspected that nintedanib could affect Wnt signaling through inhibiting Src activation in myofibroblasts.…”
Section: Nintedanib Suppressed Wnt-induced Src Activation and B-catenmentioning
confidence: 67%
“…Src kinase has previously been shown to be required for bcatenin phosphorylation at tyrosine residue 654 (Y654) and the initiation of EMT, and it has been correlated with increased b-catenin-dependent transcription in both A549 cells and primary AECs (Kim et al, 2009;Ulsamer et al, 2012). As mentioned previously, nintedanib significant inhibits Src family kinases (Li et al, 2017). Thus, we suspected that nintedanib could affect Wnt signaling through inhibiting Src activation in myofibroblasts.…”
Section: Nintedanib Suppressed Wnt-induced Src Activation and B-catenmentioning
confidence: 67%
“…EMT is a process during which epithelial cells lose their epithelial cell marker such as E-cadherin and acquire mesenchymal characteristics as α-SMA and Collagen I. EMT has been con rmed to occur in several pathological processes, including tumor invasion [29] , acute renal injury [30] , and pulmonary brosis [31,32] . Here, we demonstrated that the EMT also developed in the lungs after LPS exposure, which was coincident with increased expression of EZH2 and H3K27me3; EZH2 inhibition signi cantly restored epithelial cellular markers and inhibited bro-proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts anti-pulmonary brosis activity by inhibiting broblast growth factor receptor (FGFR), platelet-derived growth factor receptor (PDGFR), and vascular endothelial growth factor receptor (VEGFR). Studies in mice found that nintedanib reduces high tidal volume mechanical ventilation-augmented epithelial mesenchymal transition and pulmonary brosis after bleomycin-induced acute lung injury (18). Nintedanib has not been used in pulmonary brosis patients with viral pneumonia treatment, but more clinical research is needed.…”
Section: Discussionmentioning
confidence: 99%